Sosialisasi Proses Pembuatan Sabun Cuci Piring Cair sebagai Peluang Usaha bagi Ibu Rumah Tangga di Desa Timbang Lawan, Kecamatan Bahorok, Kabupaten Langkat - Intan Nofitasari; Hanifa Salsabila; Sari Jamilah Rangkuti; Pinasthika Alya Disti; Muhammad Auliyah Al Ghazali ZA; Ilka Zufria (Pusat Riset dan Inovasi Nasional, 2026)
This activity was conducted in Timbang Lawan Village, located in Bahorok Sub-district, Langkat Regency, North Sumatra Province. The results of surveys and interviews with partners indicate that most residents, especially housewives, carry out activities at home, work as agricultural laborers, and engage in farming. This situation provides significant opportunities to train and educate them through programs aimed at improving economic conditions and financial independence. However, the main inhibiting factors identified are limited access to information, knowledge, and technology, which hinder their creativity in utilizing leisure time productively. The purpose of this community empowerment program is to provide education and socialization to inspire and empower the community in addressing economic problems through training in making dishwashing liquid. After this activity, it is expected that participants can reduce household expenses by no longer needing to purchase dishwashing liquid on a daily basis. Moreover, if opportunities arise, they may also identify business prospects to develop dishwashing liquid production. The expected benefit of this activity is to foster an entrepreneurial spirit among housewives in Timbang Lawan Village.